A Real-World Analysis of High-Frequency 10 kHz Spinal Cord Stimulation for the Treatment of Painful Diabetic Peripheral Neuropathy. (March 2022) - Chen, Jeffrey L.; Hesseltine, Andrew W.; Nashi, Sara E.; Sills, Shawn M.; McJunkin, Tory L.; Patil, Sandeep; Bharara, Manish; Caraway, David L.; Brooks, Elizabeth S.
Background: Diabetes is one of the most prevalent chronic health conditions and diabetic neuropathy one of its most prevalent and debilitating complications. While there are treatments available for painful diabetic peripheral neuropathy (pDPN), their effectiveness is limited. Method: This retrospective, multi-center, real-world review assessed pain relief and functional improvements for consecutive patients with diabetic neuropathy aged ≥18 years of age who were permanently implanted with a high-frequency (10 kHz) spinal cord stimulation (SCS) device. Available data were extracted from a commercial database. Results: In total 89 patients consented to being included in the analysis. Sixty-one percent (54/89) of participants were male and the average age was 64.4 years (SD = 9.1). Most patients (78.7%, 70/89) identified pain primarily in their feet or legs bilaterally. At the last assessment, 79.5% (58/73) of patients were treatment responders, defined as having at least 50% patient-reported pain relief from baseline. The average time of follow-up was 21.8 months (range: 4.3 to 46.3 months). A majority of patients reported improvements in sleep and overall function relative to their baseline. Conclusions: This real-world study in typical clinical practices found 10 kHz SCS provided meaningful pain relief for a substantial proportion of patients refractory to current pDPN management, similar to published literature. This patient population has tremendous unmet needs and this study helps demonstrate the potential for 10 kHz SCS to provide an alternative pain management approach.